Remaking the body : rehabilitation and change - Seymour, Wendy (Routledge, 1998)
In this major new contribution to the field of the sociology of the body, Wendy Seymour interviews people who have suffered profound bodily paralysis and explores their sense of an embodied self. Essential reading for rehabilitation professionals.